Mô hình quản lí phát triển xã hội tổng quát của Việt Nam từ nay đến 2030, tầm nhìn 2045 - Phạm, Văn Đức (Tạp chí Giáo dục, 2024)
The social development model and the general model of managing social development are issues of concern to leaders, managers and researchers around the world, because of their role and impact to all areas of social life. In Vietnam, during the reform period, the Communist Party and State pay special attention to building and implementing synchronous social development institutions and policies, and managing sustainable social development, to ensure social progress and justice, building a prosperous and happy country. This article explores Vietnam's general social development management model from present to 2030, with a vision to 2045. The research results show that Vietnam's general social development management model needs to be in line with the country's development model, including specific goals and characteristics to adapt to the new international context and economic, political, cultural and social situation.